Dynamic modelling of traction motor bearings in locomotive-track spatially coupled dynamics system. Issue 8 (3rd August 2022) - Liu, Yuqing; Chen, Zaigang; Wang, Kaiyun; Zhai, Wanming
Abstract : For railway locomotive, its motor bearing is one of the key components, which is likely to be damaged due to the intensified vibration conditions caused by the wheel-rail interaction and gear mesh. In this paper, a locomotive-track spatially coupled dynamics model considering the dynamic effect of the traction power transmission is established to investigate the dynamic responses of traction motor bearings. The detailed structure of the traction motor, complex internal interactions of the rolling bearing itself, time-varying gear mesh stiffness, and wheel-rail interaction are considered. The simulated results indicate that the gear mesh excitation and internal interactions of the motor bearings significantly affect the dynamic characteristics of the rotor. The motor bearing at the driving end surfers more dynamic loads, and the internal interactions between the components are more intensified than that of the bearing at the non-driving end. Moreover, the skidding phenomenon of the motor bearing at the driving end is alleviated by the greater radial load. Additionally, the wheel-rail interaction with track random irregularity will deteriorate the working conditions of the motor bearings. The modelling method and results can provide helpful theoretical guidance for the motor bearing design and structure optimization of the locomotive traction motor.